Movement Analysis of Tasks: An Update From the Academy of Neurologic Physical Therapy's Taskforce. - Tyrell, Christine M.; Judd, Dana; Riley, Nora; Hedman, Lois D.; Kleinschmidt, Lina; Doyle, Laura; Lambert, Melanie; Quinn, Lori (Journal of Neurologic Physical Therapy, 2026)
Background and Purpose: In 2013, the American Physical Therapy Association put forth a vision statement that declared that the movement system be central to physical therapy practice. Since then, the Academy of Neurologic Physical Therapy has supported this vision by creating task forces that have worked to advance the utility of movement analysis and movement diagnoses. In 2021, the Movement Analysis of Tasks (MAT) Subgroup created and defined a series of observable movement constructs and developed a systematic method for movement analysis of specific high-priority tasks. Since then, we have sought feedback across the physical therapy community through informal methods, including national stakeholder discussions, and a formal qualitative survey of 30 physical therapists in a single health system. The purpose of this project is to provide an update to the Framework for MAT based on this feedback. Summary of Key Points: The updates to the 2021 Framework for MAT include (1) presentation of a revised set of observable movement constructs that reduces redundancy, (2) proposal of a generalized method for standardized MAT that more comprehensively considers environmental and sociocultural factors during any movement-centered examination, and (3) provide guidance on how the MAT fits within the physical therapy examination and facilitates clinical reasoning. Recommendations for Clinical Practice: Through the use of case presentations, we demonstrate the use of these tools across a wide variety of patient scenarios, thereby advocating for continued professional conversation about their clinical utility. for more insights from the authors (see the Video, Supplemental Digital Content available at: http://links.lww.com/JNPT/A556; http://links.lww.com/JNPT/A557; http://links.lww.com/JNPT/A558.